Online Learning during Covid-19: What is the Most Effective Platform for Teaching and Learning Mathematics? - Mela Aziza (Edumatika : Jurnal Riset Pendidikan Matematika, 2021)
The purpose of this research was to find how the first online learning implementation in the Department of Mathematics Education in The Islamic State Institute of Bengkulu during the Covid-19 pandemic. This research was qualitative research which was conducted in July as an evaluation of the first online learning from March until July. 90 students were chosen by purposive sampling and then given an online questionnaire. The results showed that there were some mathematical courses students took in the Even Semester 2019/2020. The platforms used by lecturers while teaching Mathematics were 39.6% WhatsApp Group, 22% Google Classroom, 13.2% Cisco Webex, and 25.2 % others. Platforms that were felt effective as online learning applications were 52.7% Cisco Webex, 26.4 % WhatsApp Group, 9.9% Zoom meeting, 5.5% Google Classroom, and 5.5% others. This is felt to be effective because it does not consume a lot of data packages, has a strong signal, and can be accessed at any time (WhatsApp Group and Google Classroom). In addition, this platform can be used for live conferencing / video calls using whiteboards which are deemed effective for teaching math material (Cisco Webex). However, several obstacles were found during the implementation of online learning, namely difficulties in obtaining sufficient internet data packages; limited network; difficult assignments and assessments; less effective teaching methods; and use of multiple applications.